MANAGEMENT OF CERVICAL RESORPTION TO PRESERVE NATURAL TOOTH: A CASE REPORT - Dr. Kiran Ghatole; Dr.Pawan Diwanji; Dr.Shreeshail Indi; Dr. Ashwini Hambire; Dr. Sumapriya Sulgante; Dr. Aadil Thimwala (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Invasive cervical resorption (ICR) is a severe pathological complication, uncommon, and often aggressive form of external root resorption. Due to its resorptive nature, the tooth structure is destructed which may lead to fracture in the crown portion. The clinical features vary from a small defect at the gingival margin to a pink coronal discoloration of the tooth crown resulting in ultimate cavitation of the overlying enamel. Resorptive condition is often detected by routine radiographic examination. The treatment should aim towards the complete suppression of all resorbing tissues and the reconstruction of resorptive defect by the placement of a suitable biocompatible material. Preservation of natural tooth is the biggest challenge in case of extensive invasive resorption. This article describes a case report of ICR of anterior teeth and its management to maintain the natural tooth and esthetics of the patient.